PENGEMASAN MAKANAN LOKAL SEBAGAI PRODUK WISATA KULINER DI BALI (Jurnal Ilmiah Pariwisata; Vol 19 No 2 (2014), 2014)
This paper aims to describe the potential and opportunities of the traditional food which is processed from the local material as a cultural product. Field survey, interview and literature review conducted to collect the data, and the results were analyzed by descriptive qualitative. The traditional food is a one of the component of culture in Bali tourism development. Knowing the economic benefits by using the local food as a cultural product, has led to the idea for businesses to develop the traditional food as culinary tourism product. To distinguish Bali culinary to the other culinary, the traditional food packed not only by using the unique of ingredients but also the food is served by Balinese service. A nice attitudes and the friendly behaviors of Balinese people as strength of Bali culinary package. However, to introduce the Balinese culinary to broader scope it is need a proper strategy in marketing . In this case, the practices have to use the right media to promote the Bali culinary to people especially for tourist. The expected through packaging the traditional foods into culinary products, people can get a better life not only in the economic aspect but also in terms of socio - cultural aspects, the people would appreciate its local products.
Keywords: Local Food, Product, Tourism Culinary, Bali